1991
DOI: 10.1083/jcb.114.4.689
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular targeting of the insulin-regulatable glucose transporter (GLUT4) is isoform specific and independent of cell type.

Abstract: . Insulin stimulates glucose transport in adipocytes via the rapid redistribution of the GLUT! and GLUT4 glucose transporters from intracellular membrane compartments to the cell surface. Insulin sensitivity is dependent on the proper intracellular trafficking of the glucose transporters in the basal state. The bulk of insulin-sensitive transport in adipocytes appears to be due to the translocation of GLUT4, which is more efficiently sequestered inside the cell and is present in much greater abundance than GLU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
80
1

Year Published

1993
1993
2009
2009

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(87 citation statements)
references
References 41 publications
6
80
1
Order By: Relevance
“…The expression of GLUT1 and GLUT4 in several cell types has demonstrated that, in spite of 65% identity in amino acid sequence, each isoform possesses distinct information conferring subcellular targeting (18,23,28,35). Experimental strategies based on the construction of chimeric transporter proteins have led to identification of several structural domains implicated as critical to the intracellular sequestration of GLUT4 (11,27,29,30,43).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of GLUT1 and GLUT4 in several cell types has demonstrated that, in spite of 65% identity in amino acid sequence, each isoform possesses distinct information conferring subcellular targeting (18,23,28,35). Experimental strategies based on the construction of chimeric transporter proteins have led to identification of several structural domains implicated as critical to the intracellular sequestration of GLUT4 (11,27,29,30,43).…”
Section: Discussionmentioning
confidence: 99%
“…This binding is saturable and competitively inhibited by peptide 480±492 [19]. The antiserum cross-reacts with the HepG2 glucose transporter [20] as well as with GLUT1 in Caco-2 cells [21].…”
Section: Methodsmentioning
confidence: 99%
“…The glucose transporter 4 (GLUT4) is the key signaling molecule that coordinates glucose conversion and metabolism with glucose transport. In response to a signal, GLUT4 is translocated from the cytoplasm to the plasma membrane, where it facilitates the entry of glucose into the cell and produces a marked cellular response [9,10] . When pathogenic factors disturb the translocation of GLUT4, the cells cannot utilize glucose, which accumulates and causes the harmful condition known as "glucose toxicity" [11] .…”
Section: Introductionmentioning
confidence: 99%